Roles of steroid sulfatase in brain and other tissues - Kříž, L; Bičíková, M; Hampl, R (Physiological research, 2008)
Steroid sulfatase (EC 3.1.6.2) is an important enzyme involved in steroid hormone metabolism. It catalyzes the hydrolysis of steroid sulfates into their unconjugated forms. This action rapidly changes their physiological and biochemical properties, especially in brain and neural tissue. As a result, any imbalance in steroid sulfatase activity may remarkably influence physiological levels of active steroid hormones with serious consequences. Despite that the structure of the enzyme has been completely resolved there is still not enough information about the regulation of its expression and action in various tissues. In the past few years research into the enzyme properties and regulations has been strongly driven by the discovery of its putative role in the indirect stimulation of the growth of hormone-dependent tumors of the breast and prostate.
Keywords: nervová tkáň; Hydrolysis; Cholesterol; Gene Expression Regulation, Enzymologic; mozek; Steryl-Sulfatase; Animals; Gonadal Steroid Hormones; Humans; steryl-sulfatasa; Nerve Tissue; lidé; pohlavní steroidní hormony; cholesterol; Brain; hydrolýza; zvířata; regulace genové exprese enzymů